Level of Satisfaction in Geriatrics by Physiotherapy Treatment for Musculoskeletal Conditions - Huma Akhtar, Agha Salman Khan, Abdullah Nawaz, Ayesha Farooq, Nimra Ijaz, Sadaf Waris (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Patient Satisfaction is a standard which measures the level of contentment patients get after having a physiotherapy treatment for the musculoskeletal conditions. Mostly, geriatric population has a greater tendency to suffer from musculoskeletal problems so the research we conducted was purely based upon the satisfaction among elderly people in Pakistan. Objective: The purpose of this study was to check the level of patient satisfaction with musculoskeletal physical therapy treatment and the factors which influence patient satisfaction. Methodology: A cross sectional study using a validated outcome measurement tool (patient satisfaction questionnaire); designed by Arcade university of Applied Sciences in Finland. The Questionnaire comprised of 20 questions and terms used in questionnaire were 1-totally dissatisfied, 2- dissatisfied, 3- neutral, 4- satisfied, 5- totally satisfied. The researcher directly interviewed 400 patients in government hospitals of Punjab like Lahore, Sialkot, Faisalabad, Gujranwala and Multan during the time period of June 2020 to Nov 2020. The research included patients with musculoskeletal problems varies between the ages of 54-74 years. Results were analyzed by SPSS version 21. Results: The results were analyzed by SPSS Statistics 21, demonstrated Totally Dissatisfied 22%, Dissatisfied 31%, Neutral 13%, Satisfied 19% and Totally Satisfied were 15% with physiotherapy services. Conclusion: This outcome of the study concluded a high level of dissatisfaction of 22% in geriatrics by physiotherapy treatment for musculoskeletal conditions. The results of this study concluded that patient centered approach was not followed by physiotherapist and hence it leads to high level of dissatisfaction in geriatrics.